Pharmacological action of Hedysarum polysaccharides: a review - Gao, Xiang; Ren, Chunzhen; Li, Linyu; Zhao, Huilin; Liu, Kai; Zhuang, Mengjie; Lv, Xinfang; Zhi, Xiaodong; Jiang, Hugang; Chen, Qilin; Zhao, Xinke; Li, Yingdong (Frontiers in Pharmacology, 2023)
Hedysarum, a traditional Chinese herbal medicine and food with a long history of clinical application, is used to improve health conditions and treat various diseases. Hedysarum polysaccharides (HPS), i.e., flavonoids, saponins, and alkaloids, are the primary components of Hedysarum. HPS is the most important natural active ingredient of Hedysarum, which has many pharmacological effects. At present, HPS has shown great potential in the development of drugs to treat different illnesses like tumors, diabetes, cardiovascular diseases, Alzheimer’s disease, and fibrosis. Here, the extraction, separation, and content determination methods of HPS, as well as the research on the chemical components of HPS, have been reviewed. More importantly, we reviewed the anti-inflammatory pharmacological effects of HPS, such as inhibition of inflammatory factors and NF-κB signaling pathway; antitumor activity through apoptosis induction in tumor cells and blocking tumor cell proliferation and metastasis; antioxidant effects; regulation of various cytokines and immune cells; regulation of blood sugar levels, such as in type I and type II diabetes and in diabetic complications; improvement in symptoms of Alzheimer disease; anti-aging and anti-fibrosis properties; and improvement in cerebral ischemia-reperfusion injury. This review lays the theoretical groundwork for future research on the structure, mechanism, and clinical application of HPS.